Politik dan Nilai-Nilai Pendidikan: (Kajian Fenominologis terhadap Praktik Politik dalam dunia Pendidikan di Kecamatan Karang Penang Kabupaten Sampang) - M Mansyur. Muhammad Juhri (Prodi PAI Fakultas Tarbiyah IAI Miftahul Ulum, 2022)
The close relationship between education and politics can have a positive and negative impact on the development of education. The positive impact that can be generated from the relationship between the two is that the government as a holder of an important role in politics can provide subsidies to education. The guaranteed value of education will produce ethics and politics that are competent towards a good democracy. This study uses a qualitative approach with a phenomenological type of research through several data collection techniques, namely: interview, observation and documentation techniques. The results of this study indicate that, first, the political development in Karang Penang Subdistrict, Sampang Regency is quite rapid, it's just that people view politics as dirty and far from religious norms. Second, the development of Islamic religious education values ​​in Karang Penang District, Sampang Regency, is quite fast, both carried out by teachers through Islamic religious education activities in schools and carried out by religious leaders or asatidz in recitation activities. Islam is carried out by religious leaders in the community. Third, political developments in building the values ​​of Islamic religious education in Karang Penang sub-district, Sampang district, are very supportive of the development of Islamic religious education values. The people's representatives who sit in the Sampang Regency DPRD from the Electoral District of Karang Penang Subdistrict play an active role in building the values ​​of Islamic religious education throughout the Karang Penang Subdistrict in the form of repairing and procuring prayer rooms and new school buildings or classrooms.